Influence of experimental temperatures on drying kinetics of Theobroma speciosum tea flowers - Mar, Josiana Moreira; Carolino, Adriano de Souza; Correa, Renilto Frota; Kinupp, Valdely Ferreira; Sanches, Edgar Aparecido; Campelo, Pedro Henrique; Bezerra, Jaqueline de Araujo (Food Science and Technology, 2025)
Drying is a crucial step in ensuring the quality of teas, as it can alter their chemical composition and organoleptic characteristics. In the present study, we examined the effects of different drying temperatures (ranging from 60 to 90°C) using hot air drying (HAD) on Theobroma speciosum flowers concerning drying kinetics, color, digestibility, and antioxidant capacity. From the obtained curves, we analyzed the physical aspects of T. speciosum, along with the moisture loss throughout the process, and the impact of different temperatures. This revealed that the Midilli mathematical model was the most suitable, where a set of equations was used to predict the analysis method’s behavior. The results demonstrated that drying at 60°C was more effective in terms of drying rates, diffusivity, and bioactive compound content, making it a promising option for the pre-treatment of T. speciosum flower tea.